A call for implementing the AOSIS declaration on capacity development in small island developing states - Vanessa P. Lopes; Diva J. Amon; Kathryn Audroing; Nellie Catzim; Harriet Harden-Davies; Kahlil Hassanali; Angelique Pouponneau; Katy Soapi; Sheena Talma; Marjo Vierros (Marine Policy, 2026)

Perspectives from Developers and Users of the GOA-ON in a Box Kit: A Model for Capacity Sharing in Ocean Sciences - Alexis Valauri-Orton, Valauri-Orton; Kaitlyn Lowder; Kim Currie; Christopher Sabine; Andrew Dickson; Sophie Chu; Alberto Acosta; Francis Asuquo; Rafael Bermudez; Ulrich Bilounga; Kishore Boodhoo; Benjamin Botwe; et al. (Oceanography, 2025)
Providing reliable instrumentation that enables collection of high-​quality, comparable data is one of the most challenging aspects of establishing ocean acidification monitoring programs. This is especially true for under-resourced countries, where such data are mostly unavailable. In 2016, The Ocean Foundation (TOF) worked with international bodies, including the International Atomic Energy Agency’s Ocean Acidification International Coordination Centre and the Global Ocean Acidification Observing Network (GOA-ON), and subject matter experts to develop a set of equipment known as the “GOA-ON in a Box” kit (The Ocean Foundation, 2017). This comprehensive kit provides researchers with everything needed—down to specialized rubber bands—to obtain weather-quality carbonate system measurements as defined by GOA-ON (Newton et al., 2015). Data are generated from spectrophotometric measurements of pHT and manual titrations for total alkalinity from discrete samples as well as in situ sensors, the iSAMI-pH and a CTD. The kit’s modular design, composed of nearly 100 unique items, makes it much less expensive than comparable integrated systems and allows for easier troubleshooting and replacement of supplied spare components.

The Ocean Foundation’s Ocean Science Equity Initiative: An Example of a Comprehensive, Intentionally Co-Designed Capacity Development Effort - Alexis Valauri-Orton; Brian Arbic; Marcia Creary-Ford; Kaitlyn Lowder; Edem Mahu; Courtnie Park; Katy Soapi; Aileen Tan Shau Hwai (Oceanography, 2025)
The Ocean Foundation’s Ocean Science Equity Initiative—EquiSea—was founded in 2022 to address systemic inequities in ocean science capacity and opportunities. It provides financial support for projects, coordinates capacity development activities, fosters collaboration and co-financing of ocean science, and supports the development of low-cost ocean science technologies. The EquiSea strategic framework was co-developed with input from more than 200 ocean science practitioners in more than 35 countries. The authors of this article are those who played the most active roles in EquiSea’s development.